Feminism and its discontents : a century of struggle with psychoanalysis - Buhle, Mari Jo, 1943- (Harvard University Press, 1998)
An ambitious and highly engaging history of ideas, Feminism and its Discontents brings together far-flung intellectual tendencies rarely seen in intimate relation to each other - and shows us a new way of seeing both.